Better Living Through Tourism’s Improvement and Homestay: A Study Case of Tegaren - Adnyana, Made Bambang; Mijiarto, Joko; Nuryananda, Praja Firdaus; Setiyowati, Arin (Graduate School, Universitas Brawijaya, 2023)
This article is the result of field research conducted in Tegaren, a tourism village in Trenggalek, East Java, Indonesia. Tegaren has become a tourism village that consistently ranks among the top 500 in the Anugerah Desa Wisata Indonesia in 2022 and 2023. This study examines how tourism growth in Tegaren impacts the quality of life through homestays and small enterprises. As one of the outstanding tourism villages in Trenggalek, Tegaren has interesting tourism developments to study. By using interviews, observation, and literature studies, the authors collected data from several village representatives. The collected data is then interpreted using qualitative analysis methods. The results obtained were then verified using the Tourism Area Life Cycle (TALC) concept and the Better Life Index for measuring quality of life. Authors also use an asset-based community development (ABCD) approach to get qualitative data as accurately as possible. This article also presents the results of research by the authors, revealing that Tegaren people are directly affected by the growing tourism business in the village. These community components include besek farmers and homestay business owners or lodging accommodations in Tegaren. This study demonstrates how local ecotourism can improve the quality of life for residents. However, there is still much that needs to be improved in this study, which is expected to be carried out in further research.